A Post-Editing of Translation Process by Google Translate: Metacognitive and Cognitive Study - Utomo, Aries (Universitas Galuh, 2025)
This study aims (1) to analyze the translator's metacognitive and cognitive strategies during the post-editing of English-Indonesian Google Translate outputs and (2) to analyze the translator's metacognitive and cognitive strategies during the post-editing of Indonesian-English Google Translate outputs. This study was qualitative research. One person was involved in this study, and the data used were one translated Indonesian-English text and one translated English-Indonesian text. To analyze the data, several steps were taken: transcribing the video, analyzing the description, considering strategies, displaying findings, and concluding. Based on the findings, it was found that the metacognitive and cognitive strategies of English-Indonesian Google Translate outputs during post-editing include Identifying and Correcting Errors, Revising, and Rereading. Cognitive strategies, such as Elaborating Ideas, Contrasting, Summarizing, Self-Questioning, Identifying Key Ideas, Expressing Opinions, Reaffirming, Connecting Ideas, Selecting Ideas, Rewriting, and Looking for Information were also noted. Reasoning strategies were not found during the post-editing of the English-Indonesian text. For the metacognitive strategies used by the translator for Indonesian-English Google Translate outputs during post-editing, the following were identified: Identifying and Correcting Errors, Revising, and Rereading. Cognitive strategies included: Elaborating Ideas, Contrasting, Summarizing, Self-Questioning, Expressing Opinions, Reaffirming, Connecting Ideas, Selecting Ideas, Rewriting, and Looking for Information. Key ideas and strategies were not identified during the post-editing of the Indonesian-English translated text. Therefore, it can be concluded that post-editing using a translation machine like Google Translate is more accurate than others.